Artificial intelligence, drug repurposing and peer review - Levin, Jeremy M; Oprea, Tudor I; Davidovich, Sagie; Clozel, Thomas; Overington, John P; Vanhaelen, Quentin; Cantor, Charles R; Bischof, Evelyne; Zhavoronkov, Alex (Nature biotechnology, 2020)
Can traditional computational analysis and machine learning help compensate for inadequate peer review of drug-repurposing papers in the context of an infodemic?